A Map Matching Algorithm for Complex Road Conditions Based on Base Station Data - Han, Boda; Tang, Xiaosheng; Hu, Zheng; Yu, Ke (International Conference on Big Data and Smart Computing, 2018)
Among the location information generated by mobile phones, except for GPS data with high precision, the base station data with low precision and high time interval is also an important basis for determining the user's actual location. While existing map matching algorithms based on base station data don't perform well at complex road conditions such as parallel roads or road intersections. Thus, a map matching algorithm based on Hidden Markov Model (HMM) was presented in this paper. By taking the attributes of road segment, the driver's driving speed and driving directions into consideration, to a certain degree, the algorithm can deal with the parallel roads and the road intersection situation effectively. Theoretical analysis and experimental test of this paper evaluated the proposed algorithm with the real base station data in Beijing. The result shows that the map-matching accuracy of our algorithm is higher than that of the prior art.